Aplikasi Effective Microorganism 10 (Em10) untuk Pertumbuhan Ikan Lele Sangkuriang (Clarias gariepinus var. Sangkuriang) di Kolam Budidaya Lele Jombang, Tangerang - Elpawati Elpawati; Dianna Rossyta Pratiwi; Nani Radiastuti (Al-Kauniyah: Jurnal Biologi, 2015)
The catfish is a fish that is widely cultivated and consumed in Indonesia. The Catfish growth depand on by the availability of food and water quality. EM4 and EM10 are an example of liquid biofertilizer. The addition of EM4 in the fish pond can help the growth of the fish and maintain of the water quality. While the test of EM10 has not been done on fishery fields. The purpose of this study was to determine the effect of EM10 fertilizers on of sangkuriang catfish (Clarias gariepinus Var. sangkuriang) growth and water quality. This research was conducted in February-March 2014. Research using completely randomized design with 7 treatments and 3 replications. The treatments tested were control (A), EM4 10 ml (B), EM4 20 ml (C), EM4 30 ml (D), EM10 10 ml (E), EM10 20 ml (F), and EM10 30 ml (G ). Analysis of data were using ANOVA followed by Duncan test if there is a real effect (ᾱ = 0.05). EM10 fertilizers at concentration of 20 ml could affect to the specific growth rate on catfish in 7 days maintenance, the concentration of 10 ml at 14 days of villa maintenance and the concentration of 30 ml at 28 days of maintenance. EM10 fertilizers can affect the weight growth of catfish. Fertilizer EM10 can maintain the temperature of the water.